Stimuli-responsive prodrug chemistries for drug delivery - Taresco, Vincenzo; Alexander, Cameron; Singh, Nishant; Pearce, Amanda K. (Wiley, 2018)
Research into advanced therapeutic materials is of growing importance worldwide, particularly in the disease areas of infection, neurodegeneration, and oncology. Advances have been made in treating these diverse pathologies but there still remain many challenging areas. Amongst the most difficult are those involving highly potent and/or cytotoxic agents which present the inherent problem of adverse off-target effects. Of key importance is to widen the therapeutic window for such agents by reducing access to non-diseased cells and enhancing release at targeted sites. Spatiotemporal controlled release can be achieved by exploiting physical, chemical, or biological stimuli present at the specific diseased area. A crucial strategy involves drug-carrier linkages able to respond to physiological or biochemical stimuli present in the disease region, and there is now significant literature on (polymeric) prodrugs based on the drug + carrier + cleavable linker philosophy, predominantly for cancer applications. The authors therefore focus this mini-review primarily on single/multi stimuli-responsive prodrugs for cancer therapies, covering prominent examples of prodrug chemistries used to endow polymers with controlled and site-specific drug delivery properties. Additionally, the possibilities for exploiting similar approaches to disease-associated stimuli present in bacterial and viral infections, inflammatory and immune diseases, and in degenerative disorders are emphasized.